H∞ filter with fuzzy logic estimation to refrain finite escape time - Bakiss Hiyana, Abu Bakar; Hamzah, Ahmad (Springer, 2021)
In this paper, a H∞ Filter with Fuzzy Logic (FHF) based on mobile robot localization and mapping is proposed to effectively prevent the Finite Es-cape Time (FET) issue in H∞ Filter (HF). The capabilities of HF to offer better solution than Kalman Filter (KF) is limited by the shortcomings of Finite Escape Time. FET define as a state that can go infinite in normal condition that lead to in accurate estimation result, with the present of FET, the estimation cannot be totally guarantee. Therefore, it is essential to guarantee no FET is observed in the state covariance on its update. A new FHF is developed for this matter by using fuzzy logic approach. The analysis is done by implementing the Fuzzy Logic technique with triangular membership. The simulation result show that Fuzzy Logic effectively avoid the FET from appear and simultaneously improve the estimation between mobile robot and the landmark.